Public School Superintendent Sagacity: A Foundation for Financial Leadership (Journal of School Administration Research and Development, 2022)
In an era of accountability, competition for student enrollment, and the necessity to balance district budgets, district leaders are seeking to thrive despite these legitimate stressors. Among the responsibilities of a superintendent, financial leadership balanced with instructional leadership is critical to the success of a school district and the leader. This study sought to explore how superintendents construct their financial leadership savvy and develop financial sagacity in a context where they are under stressful and ever-changing conditions. Findings from this study indicate that superintendents rely primarily on professional networks to inform their decision making and that there is a significant relationship between job experience and stress related to school finances. Researchers also identified implications for superintendents related to level of stress, the importance of professional networks and mentoring, and the essence of creative strategies aligned to financial decision making for superintendents.